PENGARUH ETIKA PROFESI, INDEPENDENSI DAN PROFESIONALISME AUDITOR TERHADAP KINERJA AUDITOR DIMEDIASI KOMITMEN ORGANISASI (STUDI KASUS PADA KANTOR AKUNTAN PUBLIK DI KOTA SEMARANG) - Rita Andini (Universitas Pandanaran, 2019)
Auditor performance is the result of work achieved by the auditor in carrying out hisduties in accordance with the responsibilities given to him and becomes one of thebenchmarks used to determine whether a work performed will be good or vice versa. Theauditor's performance is the focus of attention for the Public Accountant Office and theclient in assessing the results of the audit conducted, as well as the auditor who works inthe Public Accounting Firm in the City of Semarang. The purpose of this study was todetermine the effect of professional ethics, independence and professionalism of auditorspartially on organizational commitment and auditor performance and the influence oforganizational commitment on auditor performance. The population in this research were auditors who worked in the Public AccountantOffice in the city of Semarang and had worked for at least 4 years, with 100 respondents.The sampling technique is the census and the data analysis technique used is the 2-stageMultiple Linear Regression. Based on the results of calculations, it can be seen that professional ethics,independence and professionalism of auditors partially have a positive and significanteffect on organizational commitment and auditor performance, and organizationalcommitment has a positive and significant effect on auditor performance.It is recommended that the Public Accountant Office in the City of Semarang motivateauditors who work in their institutions to adhere to professional ethics properly, upholdindependence and increase the professionalism of their work, in order to achieveorganizational goals and increase the trust of clients who use their services.Keywords : professional ethics, independence, auditor professionalism,organizational commitment and auditor performance